Optimization Study of Sequencing Batch Reactor (SBR) Poultry Wastewater Operation in Low Influent Flow Rate - Mohamad Shukri, Muhammad Amir Redzuan; Nor Haslina Hashim, (Progress in Engineering Application and Technology, 2024)
This study examines the effectiveness of Sequencing Batch Reactor(SBR) technology in treating poultry slaughterhouse wastewater. Thestudy monitored the parameters of pH, SV30, DO, AN, MLSS, COD, andBOD to evaluate the efficiency of the biological treatment process. Theresults suggest that SBR technology can be effective in removing organicmatter and nitrogen from poultry wastewater. The comprehensiveresults reveal the effectiveness of SBR in removing suspended solids,microorganisms, nitrogen, and organic matter from the wastewater. Thestudy underscores the importance of monitoring these parameters forassessing treatment efficacy and highlights the potential of SBR as apromising solution for sustainable poultry wastewater treatment.However, the study also highlights the importance of continuousmonitoring and optimization of treatment processes to ensure theireffectiveness.